Microscopic, macroscopic and thermal impact of argon plasma, diode laser, and electrocoagulation on ovarian tissue - Stefanovic, Stefan; Sütterlin, Marc; Gaiser, Timo; Scharff, Christoph; Neumann, Marcel; Berger, Laura; Froemmel, Niklas; Tuschy, Benjamin; Berlit, Sebastian (In vivo, 2023)
Background/Aim: To compare the microscopic, macroscopic and thermal damage inflicted to ovarian tissue by conventional monopolar and bipolar energy, argon plasma coagulation (APC) and diode laser. Materials and Methods: Bovine ovaries were used as a substitute for human tissue and subjected to the four aforementioned techniques and the inflicted damage was measured. Sixty fresh and morphologically similar cadaveric bovine ovaries were divided into five equal groups, each group was subjected to one of the following energy applications for both 1 and 5 s: Monopolar, bipolar electrocoagulation, diode laser, preciseAPC® and forcedAPC®. Ovarian temperatures were measured at 4 and 8 s after treatment. Formalin-fixed ovarian specimens were examined by pathologists regarding macroscopic, microscopic and thermal tissue damage. Results: None of the ovaries reached the temperature producing severe damage (40°C) after 1 s of energy transfer. Heating of adjacent ovarian tissue was least pronounced when preciseAPC® and monopolar electrocoagulation were applied (27.2±3.3°C and 28.2±2.9°C after 5 s of application, respectively). Conversely, 41.7% of the ovaries subjected to bipolar electrocoagulation for 5 s overheated. ForcedAPC® resulted in the most pronounced lateral tissue defects (2.8±0.3 mm after 1 s and 4.7±0.6 mm after 5 s). When the modalities were applied for 5 s, the electrosurgical instruments (mono- and bipolar) and preciseAPC® induced similar lateral tissue damage (1.3±0.6 mm, 1.1±1.6 mm and 1.2±1.3 mm, respectively). preciseAPC® created the shallowest defect of all the techniques (0.05±0.1 mm after 5 s of application). Conclusion: Our study hints at superior safety profiles of preciseAPC® and monopolar electrocoagulation compared to bipolar electrocoagulation, diode laser and forcedAPC® for ovarian laparoscopic surgery.